Study on the Design and Optimization of the Mix Proportion for High-Grade Concrete for the Pylon of a Long-Span Suspension Bridge - Xiaoliang Zhu; Baoan Quan; Sheng Fang; Hao Wei; Junchen Zhao (预应力技术)
In this paper, an in-depth study was conducted on the design and optimization of the mix proportion of C55 high-fluidity pumped mass concrete for the northern pylon of the Longtan Yangtze River Bridge. During the mix proportion trial and initial adjustment phase, the W/B ratio was determined in accordance with relevant standards, and the performance indicators of the aggregates were comprehensively considered to select coarse and fine aggregates based on scientific evidence. The range of mineral admixture proportions was determined on the basis of performance and cost considerations. Through a series of experimental studies, the influence of various factors on the workability of concrete was determined, and the initial mix proportion was preliminarily established. Further exploration of the effects of cement type and functional aggregates revealed that the workability of the project cement was inferior to that of Onoda cement, but the concrete was not replaced for cost reasons. Functional aggregates can enhance concrete performance from various aspects, but may slightly reduce compressive strength. The multiobjective mix proportion was further optimized and subjected to performance verification. After functional aggregates were added to the optimized mixture, the concrete exhibited excellent workability and met the strength requirements. Thermal insulation aggregates effectively mitigated an increase in concrete temperature, whereas heat-storage aggregates provided good initial temperature control during pouring. Through more than 20 sets of experiments, multistep optimization, and verification, the key factors and their mechanisms in mix proportion design were clarified.This study provides a systematic methodology and practical basis for the design of high-fluidity mass concrete, ensuring the safety and durability of projects.